Arabic translation and psychometric validation of the Problem-Solving Decision-Making scale: A cross-sectional study in Saudi Arabia - Nouf Sahal Alharbi; Nouf Nasser Alsaheil; Jwaher Haji Alhaji; Sara Mohammed Karsha (PLoS ONE, 2026)
The Problem-Solving Decision-Making scale was originally developed in English to assess patient preferences across three domains: mortality, morbidity, and quality of life. This study aimed to translate, culturally adapt, and psychrometrically validate an Arabic version of the Problem-Solving Decision-Making scale using a sample of 505 adults from the general Saudi population. The translation followed World Health Organization guidelines for instrument translation and validation. Exploratory and confirmatory factor analyses were conducted to examine the underlying factor structure. Internal consistency was assessed using Cronbach’s alpha, while construct validity was evaluated through average variance extracted and the Fornell–Larcker criterion. Measurement invariance across sex was examined using multigroup confirmatory factor analysis. The Arabic version demonstrated strong psychometric properties. Exploratory factor analysis identified a four-factor structure explaining 56% of the variance, which showed good model fit (χ²/df = 3.22, CFI = 0.991, TLI = 0.990, SRMR = 0.070, RMSEA = 0.081). All factors exhibited satisfactory internal consistency. Convergent and discriminant validity were supported. Measurement invariance was established across sex, and latent mean comparisons indicated that females scored significantly higher than males across all four factors. These findings support the reliability and validity of the Arabic Problem-Solving Decision-Making scale and highlight its suitability for assessing patient involvement preferences in Arab population.